PROMOSI KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN DAN KETRAMPILAN IBU MENYUSUI - Isna Aglusi Badri; Nahrul Hayat; Roza Erda (JURNAL ABDI MERCUSUAR, 2022)
Background : Mother's Milk (ASI) is the most beautiful gift from the mother to those secreted by both breast glands in the form of natural food or the best nutritious and high-energy milk which is easily digested and contains a balanced and perfect nutritional composition for the growth and development of the baby which is available at any time. The causes of failure of exclusive breastfeeding are the lack of knowledge of mothers about breastfeeding and breastfeeding, working mothers, no support from the family, improper breastfeeding techniques and the myth that diluted milk is not good for babies. Method : This activity was attended by cadres and mothers who had babies and toddlers as many as 32 people in the Working Area of ??the Galang Health Center, Galang District. This activity was carried out using health promotion methods with counseling and practicing how to breastfeed properly. Result: The result that can be taken from this activity is to improve the quality of life of the baby when the knowledge of the mother regarding the correct way of breastfeeding can reduce infant morbidity and mortality. Breast milk can guarantee good nutritional status so that it can protect infants and children from infectious diseases such as diarrhea, otitis media and acute lower respiratory tract infections.